2010
DOI: 10.1002/anie.201001804
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Surface Compositions of Stoichiometric Mixed Oxide Compounds

Abstract: Surface-oxide films are present in many types of oxidecontaining materials, such as grain boundaries in ceramics, [1] interfaces in ceramic-ceramic [2] and metal-oxide systems, [3] and affect their materials and transport properties. In heterogeneous catalysis, the properties of the outermost surface layer are of prime importance because they control the catalytic performance. Although bulk mixed-metal oxide catalysts are widely used in industrial selective oxidation processes, [4,5] not much is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…We can identify three regimes of (T, p(O 2 )) where the surface exhibits different features and gain a deeper understanding of what drives these surface changes. Beside our new insight into Sr segregation, we propose that such a model would also be useful for other complex nonstoichiometric oxides [70] employed in catalysis to predict surface structure of complex catalyst materials under operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…We can identify three regimes of (T, p(O 2 )) where the surface exhibits different features and gain a deeper understanding of what drives these surface changes. Beside our new insight into Sr segregation, we propose that such a model would also be useful for other complex nonstoichiometric oxides [70] employed in catalysis to predict surface structure of complex catalyst materials under operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In heterogeneous catalysis, mixed metal oxides (MMOs) play a very important role because of their versatile chemical and physical properties and wide applications in the field of catalysis and technology. [1][2][3][4][5] Mixed metal oxides represent one of the most important and widely employed classes of solid catalysts, either as active phases or supports. Mixed oxides are applied both for their acid-base and redox properties and constitute the largest family of catalysts in heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, reduced redox catalyst is highly K-enriched and the presence of surface Mn was reduced by ~5-folds. The surface enrichment of K on reduced samples was further confirmed with LEIS spectroscopy, which can detect the composition of topmost surface layers of a redox catalyst 49 . LEIS confirmed that the reduced samples are enriched with K and surface Mn/Fe are significantly suppressed (Fig.…”
Section: Resultsmentioning
confidence: 75%